Teacher Professional Identity, Work Engagement, and Emotion Influence: How do They Affect Teachers’ Career Satisfaction - Gong, Yue; Wang, Lei (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2023)
Teachers’ behaviours significantly influence students’ learning outcomes but also play an important role in national development and construction. However, few studies have attempted to investigate the interrelationships between teachers’ professional identity, work engagement, emotion, and attitude towards career satisfaction. This study aims to explore the effect of professional identity and emotion on work engagement and career satisfaction separately and to investigate the influence of work engagement on attitude and, subsequently career satisfaction. A convenience sampling technique includes 221 valid questionnaires that were subjected to descriptive analysis followed by subsequent empirical testing of the populated hypotheses using SPSS and AMOS. Results showed that professional identity and emotion positively influence work engagement and career satisfaction respectively. Work engagement positively influenced attitude and, subsequently career satisfaction. Last, the theoretical and practical implications and limitations were discussed.